Is it time to abolish estate duty in South Africa? a comparative look at global trends in levying death taxes and the feasibility of suggested changes to South Africa’s current regime - Thorpe, Lindsey Lee (Department of Commercial Law, 2015)
This dissertation examines the current system of taxation that is imposed in South Africa on the death of a taxpayer. The main focus of the research, among others, is on the issues associated with a taxpayer having to pay both estate duty and capital gains tax upon his or her death, resulting in a form of 'double taxation', and whether a different system of taxation should be implemented in South Africa. The two main taxes imposed on death in South Africa are studied and arguments for and against the imposition of death taxes are considered. In order to determine what the most fair and reasonable tax system for South Africa would be, various taxation models of other jurisdictions are examined, namely those followed by the United States, the United Kingdom, Canada, Australia, India, Botswana and the Netherlands. Suggested alternatives and their suitability are identified, such as the possibilities of retaining estate duty and 'forgiving' capital gains tax on death (as is done in the United States, United Kingdom, Australia, India and Botswana); abolishing estate duty and imposing only capital gains tax on death (a system followed by Canada); replacing estate duty with an inheritance tax (like in the Netherlands) or retaining the current system in place. Ultimately, it is decided that South Africa should not abolish estate duty or rely solely on capital gains tax or implement a system of inheritance tax. Instead, we should retain the current system as there are already concessions provided by the legislature which aid the majority of South Africans and guard against unfair results occurring in the winding up of their estates. A suitable alternative would be to rely only on capital gains tax, but any amendments would result in major changes to current legislation. Furthermore, it is important to first ascertain whether relevant stakeholders, such as the South African Revenue Service or the Master of the High Court, would have the necessary resources, capacity and time to train staff, educate taxpayers and update their current systems in order to successfully implement these changes and efficiently process deceased estates.